Job strain among Malaysian office workers of a multinational company - Maizura, H.; Retneswari, M.; Moe, H.; Hoe, V.C.W.; Bulgiba, Awang (2010)
Aims To investigate the prevalence and factors associated with high job strain among office workers of a multinational company in Malaysia. Methods A cross-sectional study was conducted in November 2007 among 470 eligible workers. Respondents self-administered the Job Content Questionnaire downloaded from the company's intranet. A median-split procedure was applied to create four groups according to the Job Demand-Control Model: active, passive, high and low job strain. Logistic regression models were used to investigate the associations between socio-demographic, occupational and psychosocial factors and high job strain. Results A total of 356 questionnaires were received (response rate 76). Twenty-one per cent of respondents were in the high job strain group, 35 were in the passive group, whereas 26 and 17 of workers were in the low strain and active groups, respectively. After controlling for confounders, three factors were found to be associated with high job strain: male workers (adjusted OR 1.94, 95 CI 1.04-3.64), working > 48 h per week (adjusted OR 2.51, 95 CI 1.44-4.39) and job insecurity (adjusted OR 1.14, 95 CI 1.02-1.27). One protective factor for high job strain was the scale 'created skill', which is part of skill discretion (adjusted OR 0.70, 95 CI 0.57-0.86). Conclusions About one in five workers in this study experience high job strain. Work improvement measures include reducing long working hours and job insecurity and giving workers the opportunity to learn, use creativity and develop abilities.